Experimental Activation Energy for Solid Phase Crystallization of Amorphous Silicon Thin Films at Elevated Temperatures Using Vertical-Cavity Surface-Emitting Laser-Based Infrared Heating. (1st April 2022) - Noh, Youngsu; Il Lee, Myeong; Park, Seungho; Hwang, Jin-Ha
Abstract : Vertical cavity surface-emitting lasers (VCSELs) were applied to the rapid heating of amorphous Si (a-Si) thin films using high-power infrared illumination at a wavelength of 980 nm, allowing for a high heating rate of up to 200 °C s −1, temperature control of less than 0.1 °C and temporal resolution of 0.1 s. The refined temperature control enabled us to accurately investigate the rapidly evolving period of crystallization in a-Si at a fast speed. The crystallinity and surface morphology were probed using Raman spectroscopy, UV–visible spectroscopy, and atomic force microscopy. The temperature-dependent crystallinity was quantified by fitting the annealing duration time with a sigmoidal curve. Based on the crystallization times in association with the Arrhenius relation, the activation energy for crystallization was calculated to be 2.6 eV, which is in excellent agreement with those obtained for low-temperature solid-phase crystallization.